Experiências Comparadas na Educação do Campo entre Brasil e Cuba e as Possibilidades de Formação Omnilateral na América Latina - Villela, Fabio Fernandes [UNESP] (My University, 2012)
This text aims to present the challenges and opportunities of omnilateral formation in Latin America as elaborated in Villela (2009-2010). This work has the horizon systematize the educational practices of the “Third World “, i.e. originating from the educational experience of Latin America, Africa and Asia. In the struggle for emancipation, these countries have built and are building unique educational practices. In this sense, we start questioning the historical and theoretical topic, omnilateral formation, and deployment, we discuss the Latin American school and omnilateral formation. We question specifically issues relating to intellectual and educational organization working in the “field schools” in Cuba (1960-1975). The issue of “intellectual and organizational culture”, in a Gramscian perspective (Gramsci, 2000), was addressed in several papers throughout our academic career (Villela, 2003, 2008, 2009-2010). In order to further these issues, we address the challenges of formation for children and rural youth in Latin America. By analyzing the educational practices in the education field, emerges the theme of contemporary global justice.

Este texto tem por objetivo apresentar os desafios e as possibilidades da formação omnilateral na América Latina conforme elaborado em Villela (2009-2010). Este trabalho tem por horizonte sistematizar as práticas educativas do “Terceiro Mundo”, isto é, originadas da experiência educacional dos países da América Latina, África e Ásia. No processo de luta pela emancipação, esses países construíram e estão construindo práticas educativas originais. Nesse sentido, partimos da problematização histórico-teórico do tema, formação omnilateral, e por desdobramento, abordamos a América Latina, escola e formação omnilateral. Problematizamos especificamente as questões relativas aos intelectuais e a organização trabalho pedagógico nas “escolas no campo” em Cuba (1960-1975). A questão dos “intelectuais e a organização da cultura”, sob uma perspectiva gramsciana (Gramsci, 2000), foi abordada em diversos trabalhos ao longo de nossa trajetória acadêmica (Villela, 2003; 2008; 2009-2010). No sentido de aprofundar tais questões, abordamos os desafios da formação de crianças e jovens do campo na América Latina. Ao analisarmos as práticas educativas em educação do campo, emerge a temática contemporânea da justiça global.
Keywords: Práticas Educativas; Educação e Trabalho; Educação do Campo; Formação Omnilateral; América Latina; Educational Practices; Education and Labour; Rural Education; Omnilateral Formation; Latin America